2012
DOI: 10.3390/v4091569
|View full text |Cite
|
Sign up to set email alerts
|

Host Cell Factors as Antiviral Targets in Arenavirus Infection

Abstract: Among the members of the Arenaviridae family, Lassa virus and Junin virus generate periodic annual outbreaks of severe human hemorrhagic fever (HF) in endemic areas of West Africa and Argentina, respectively. Given the human health threat that arenaviruses represent and the lack of a specific and safe chemotherapy, the search for effective antiviral compounds is a continuous demanding effort. Since diverse host cell pathways and enzymes are used by RNA viruses to fulfill their replicative cycle, the targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 143 publications
(184 reference statements)
2
25
0
Order By: Relevance
“…Previous studies have documented that inhibitors of cytosine triphosphate synthetase (29) and OMPD (31) exhibit antiarenaviral activity, but their potency is lower than that of ribavirin (25). We observed that the magnitude of the antiarenaviral activity of A3 was significantly higher in human A549 cells than in hamster BHK-21 cells, a finding consistent with reported cell-species-dependent differences on the antiviral activity of A3 against influenza virus (32).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous studies have documented that inhibitors of cytosine triphosphate synthetase (29) and OMPD (31) exhibit antiarenaviral activity, but their potency is lower than that of ribavirin (25). We observed that the magnitude of the antiarenaviral activity of A3 was significantly higher in human A549 cells than in hamster BHK-21 cells, a finding consistent with reported cell-species-dependent differences on the antiviral activity of A3 against influenza virus (32).…”
Section: Discussionsupporting
confidence: 81%
“…Notably, the antiviral and mutagenic activities of ribavirin could not be accounted for solely by depletion of intracellular GTP levels, which are a consequence of IMPDH inhibition (24)(25)(26)(27)(28). Several other compounds, including cytidine analogs that target cytosine triphosphate synthetase (29), analogs of adenosine that target S-adenosylhomocysteine hydrolase and interfere with the 5= cap of mRNA (30), and carbanucleoside analogs that target orotidylic acid decarboxylase (OMPD) and inhibit the conversion of OMP to UMP (31), have been shown to have antiarenaviral activities but did not exhibit advantages over ribavirin (25). Recently, a screen for inhibitors of influenza virus replication in cultured cells identified the de novo pyrimidine biosynthesis inhibitor compound A3 (32), which was found to have a broad inhibitory effect on multiplication of several other RNA viruses, including Newcastle disease virus, vesicular stomatitis virus, Sindbis virus, hepatitis C virus, West Nile virus, and dengue virus (32).…”
mentioning
confidence: 99%
“…To overcome the emergence of drug-resistant viruses, bacteria, and fungi, therapeutic strategies that aim at targeting host cell factors rather than the pathogen itself are currently pursued [110]. However, most of these novel approaches are still in very early phases of clinical trials.…”
Section: Annexins and The Host/pathogen Interfacementioning
confidence: 99%
“…Prominent examples for this are penicillin and amantadine (WHO, 2014). This is expected to be more unlikely for drugs that target host factors (Linero et al, 2012). Given that infectious diseases still account for many deaths worldwide, mainly in poorer societies, suitable therapeutic approaches are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Pathogens rely on their host and the host environmental conditions and are therefore highly adapted to both. Because of their often high mutation rate and the transfer of mobile genetic elements (Stokes and Gillings, 2011;Linero et al, 2012), viruses and bacteria acquire resistance to drugs that target pathogen components. Prominent examples for this are penicillin and amantadine (WHO, 2014).…”
Section: Introductionmentioning
confidence: 99%